Democracy with adjectives? Economic development and democracy in the Middle East - Yasun, Salih (Frontiers in Political Science, 2024)
Shadi Hamid, in his book “The Problem of Democracy, advocates for the promotion of minimalist democracy for the Middle East. Can minimalist democracy respond to the aspirations of the Arab public? Using data from the Arab Barometer (2018) survey, I emphasize that many citizens of Arab countries define democracy by its expected economic outcomes. Whether minimalist democracy can spur economic development is a puzzle. Literature on democratization and economic growth is inconclusive. In the Middle East and North Africa region, ballot box alone may not overcome significant barriers, such as overriding interest groups and corruption, to spur development. Democratic openings in the region often failed to promote expected economic growth. Therefore, while minimalist democracy would be an improvement for the current standards of governance in the region, it may fail to respond to the aspirations of the masses, making authoritarian reversion a likely outcome.